From fresh to salty: exploring water salinity tolerance in Rhinella ornata (Anura, Bufonidae) tadpoles on Brazilian Atlantic Forest - Pires, Thiago Leão; Nagai, Micael Eiji; Furtado, Raissa; Benavides-Gordillo, Sandra (Brazilian Journal of Science, 2025)
Changes in salinity levels of aquatic environments may significantly affect the distribution and abundance of many species, including amphibians. Typically, amphibians inhabit environments with low salinity. However, tadpoles of Rhinella ornata can often be found in environments in which stochastic events, such as high tides, can dramatically modify the water salinity of ponds in coastal regions. Here, we test the hypothesis that elevated salinity negatively affects the survival and latency of tadpoles of Rhinella ornata. We exposed 32 tadpoles to different salinity levels (0, 10, 18, 30 parts per thousand or ppt) and measured the time of death and latency time in individuals of two body size classes. Mortality was significantly different between intermediate and high salinity levels (18 and 30 ppt) but did not depend on body size. These results show that tadpoles of Rhinella ornata seem to be intolerant of high salinity, regardless of size. However, there was no mortality at lower salinity levels (0 and 10 ppt) and no difference in latency period between the two lower levels, implying that these tadpoles can survive in low water salinity for a short period, enabling them to swim to less brackish environments. Overall, this trait seems to be important for Rhinella ornata to tolerate shoreline environments, which are vulnerable to stochastic events that dramatically increase pond salinities.